Analysis of the Effect of Conflict and Work Stress on the Performance of Employees of PT Perkebunan ABC Asahan - Damanik, Darwin Sahat Hamonangan (Syntax Corporation Indonesia, 2023)
PT Perkebunan ABC is always encouraged to be able to achieve targets and increase the productivity of its employees. The problem in this study is whether conflict and work stress affect the performance of PT Perkebunan ABC employees with the hypothesis being conflict and work stress affect the performance of PT Perkebunan ABC employees. The theories used in this study are Human Resource Management (HRM), conflict management and organizational behavior related to conflict, work stress and employee performance. The purpose of this study is to determine what factors influence conflict and work stress on the performance of PT Perkebunan ABC employees and formulate managerial policies that can be implied in order to improve employee performance. This research is in the form of correlational research with a research population of 749 people, all of whom are Executive Employees. The analytical method used in this study is the Structural Equation Model (SEM) analysis method. The results showed that conflict was the most dominant factor affecting the performance of PT Perkebunan ABC employees. The conclusion of this study is that the most dominant factor affecting the performance of Executive Employees (Karpel) at PT Perkebunan ABC Asahan is conflict with the magnitude of the influence reaching 91%.